Malaysian Muslim consumers’ awareness, confidence, and purchase behaviour on halal meat and its products after the meat cartel scandal - Mahamad Maifiah, Mohd Hafidz; Ahmad, Anis Najiha; Azam, Siddique (Rynnye Lyan Resources, 2022)
Many issues of halal food fraud involved the misuse of halal logo and certificate, mislabeling of products, and adulteration of halal products with non-halal ingredients. The sensitivity concern pertaining to halal meat and its products, particularly regarding the incident of the meat cartel scandal that happened in Malaysia had impacted consumers’ trust and confidence, particularly among the Muslim communities. This research aimed to assess the degree of confidence and purchase behaviour among Muslim consumers on halal meat and its products following the issue of the imported meat cartel scandal. The extent of consumer awareness of the issue was also asked. The survey was performed among 1,045 Muslim consumers via a structured questionnaire to measure their awareness, confidence and purchase behaviour on halal meat and its products. The results highlighted that the issue had affected the Muslim consumers’ perception of their confidence and purchasing behaviour majorly on imported meat and meat products. In addition, the confidence and purchasing trend of consumers has also reduced towards meat products other than the Department of Islamic Development Malaysia (JAKIM) certified halal logo. Overall, the concern on the issue has impacted Muslim consumers’ behaviours towards halal meat and its products which demanded more serious attention and action to assure the halal integrity of the products.